Mathematical problem-solving abilities and reflective thinking abilities: The impact of the influence of eliciting activities models - Hartati, Suci; Bilqis, Ratu Ayu; Rinaldi, Achi (Al-Jabar: Jurnal Pendidikan Matematika, 2020)
This study aims to determine the effect of the Model Eliciting Activities (MEAs) learning model to the mathematical problem-solving abilities and the mathematical reflective thinking skills. This research is a type of Quasi Experimental Design research. Data collection techniques in this study in the form of documentation and tests at the public school in Bandar Lampung with 30 students of experiment classes and 30 students of control classes. Data analysis techniques used are the normality and homogeneity test. Testing hypothesis in this study using the Multivariate Analysis of Variance (MANOVA) test. Based on the result of this study, the calculation of the MANOVA test, it was concluded that there was an influence of the Model Eliciting Activities (MEAs) to the mathematical problem-solving abilities and the mathematical reflective thinking skills. The application of the Model Eliciting Activities to the mathematical problem-solving abilities and the mathematical reflective thinking skills has a relatively  high level of effectiveness.